2017
DOI: 10.3934/biophy.2017.3.491
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors: the evolution of structural insight

Abstract: G protein-coupled receptors (GPCR) comprise a diverse superfamily of over 800 proteins that have gained relevance as biological targets for pharmaceutical drug design. Although these receptors have been investigated for decades, three-dimensional structures of GPCR have only recently become available. In this review, we focus on the technological advancements that have facilitated efforts to gain insights into GPCR structure. Progress in these efforts began with the initial crystal structure determination of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 189 publications
0
54
0
Order By: Relevance
“…The majority of studies on isolated membrane proteins are still carried out in a detergent system; GPCR research is no exception ( Table 2 ) where well-established protocols have greatly simplified membrane extraction. The vast majority of GPCR structures deposited in the PDB have been obtained for receptors in detergent micelles [ 185 ]. Further, the proven ability to make homogeneous particles with sizes ( Figure 4 ) that relate to sufficiently rapid rotational tumbling means detergents have been a favoured system for solution NMR studies.…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…The majority of studies on isolated membrane proteins are still carried out in a detergent system; GPCR research is no exception ( Table 2 ) where well-established protocols have greatly simplified membrane extraction. The vast majority of GPCR structures deposited in the PDB have been obtained for receptors in detergent micelles [ 185 ]. Further, the proven ability to make homogeneous particles with sizes ( Figure 4 ) that relate to sufficiently rapid rotational tumbling means detergents have been a favoured system for solution NMR studies.…”
Section: Membrane Mimetic Systems For Structural and Functional Stmentioning
confidence: 99%
“…The domain orientations are constrained by the mutational data in such a way as to bring ECL2 immediately below the last module of the CRD. In GPCRs generally, ECL2 is a critical determinant of ligand interactions (55,56). ECL2 of class C GPCRs are similar in length (less than 35 residues), and the length of the linker peptide at the end of the CRD is also important for receptor activation and surface expression (57)(58)(59).…”
Section: Structural Architecture Of the Dimeric Sweet Taste Receptormentioning
confidence: 99%
“…This GPR17 model resulted much more accurate than the previous ones, due to the closest sequence identity of GPR17 with respect to P2Y 1 , compared to that shared with all the other available crystallographic templates among related class-A GPCRs (26.4%). A pairwise alignment identity matrix between GPR17 and the primary structures of other related class-A GPCR, whose structure has been solved (Gacasan et al, 2017), is reported in Supplementary Figure S5.…”
Section: Molecular Modeling and Ligand Dockingmentioning
confidence: 99%